PENGARUH PEMBESARAN DIAMETER DAN PEMOLESAN INLET PORT PADA MESIN 4 TAK 150CC SOHC - Aji, Abigunto Amoro Aji; Ivan Halim; Harry Munandar; Larasati Rizky Putri (Program Studi Teknik Mesin Universitas Tarumanagara, 2023)
Porting & polishing is the process of enlarging the diameter of the cylinder head intake and exhaust duct holes, as well as smoothing the surface. This modification is carried out manually by a mechanic who has experience. This research examines changes in diameter and surface roughness on machine performance, namely power and torque. A number of samples with volume of cylinder 148,7 cc motorbikes were ported & polished manually for 1, 2 and 3 hours. Changes in diameter and surface roughness were recorded both before and after processing. Next, using a Dynoyet 250i dynamometer, power and torque measurements were carried out. A smooth surface will cause the fuel to touch the surface and evaporate, thus increasing the mixture of air and fuel because both are in the same phase and condition. Furthermore, in the diameter change range of up to 10.36% from the initial diameter, it was recorded that the increase in power and torque could reach 8.94%. In this way, porting & polishing is able to fulfill the racers' desires for competition activities